Pathogenesis of the epigastric hernia. - Ponten JE; Somers KY; Nienhuijs SW; Ponten, J E H; Somers, K Y A; Nienhuijs, S W (Hernia, 2012)
Purpose: Epigastric herniation is a rather common condition with a reported prevalence up to 10 %. Only a minority is symptomatic, presumably the reason for the scarce literature on this subject. Epigastric hernias have specific characteristics for which several anatomical theories have been developed. Whether these descriptions of pathological mechanisms still hold with regard to the characteristics of epigastric hernia is the subject of this review.Methods: A multi-database research was performed to reveal relevant literature by free text word and subject headings 'epigastric hernia', 'linea alba', 'midline' and 'abdominal wall'. Reviewed were studies on anatomical theories describing the pathological mechanism of epigastric herniation, incidence, prevalence and female-to-male ratio and possible explanatory factors.Results: Three different theories have been described of which two have not been confirmed by other studies. The attachment of the diaphragm causing extra tension in the epigastric region is the one still standing. Around 1.6-3.6 % of all abdominal hernias and 0.5-5 % of all operated abdominal hernias is an epigastric hernia. Epigastric hernias are 2-3 times more common in men, with a higher incidence in patients from 20 to 50 years. Some cadaver studies show an epigastric hernia rate of 0.5-10 %. These specific features of the epigastric hernias (the large asymptomatic proportion, male predominance, only above umbilical level) are discussed with regard to the general theories.Conclusions: The epigastric hernia is a very common condition, mostly asymptomatic. Together with general factors for hernia formation, the theory of extra tension in the epigastric region by the diaphragm is the most likely theory of epigastric hernia formation.